Analysis of rainfall in the Metropolitan Region of Cariri and the influence of the el niño climate phenomenon - Southern Oscillation (Research, Society and Development, 2020)
Climate study is essential for understanding and monitoring atmospheric activities, such as climate change. The climate of a region undergoes several changes due to natural or anthropic factors, especially El Niño - Southern Oscillation, an anomaly that can cause financial damage in agricultural production, floods and severe droughts. Climatology and Meteorology stand out in the study of historical rainfall and climatic phenomena, which corroborate the control and understanding of atmospheric activities that influence the rains of the Northeast. In this sense, the present work aims to analyze the behavior of rainfall in the Metropolitan Region of Cariri and to relate the behavior of rainfall with the years of influence of the climatic phenomenon El Niño-Southern Oscillation, in the period from 1980 to 2019, focusing on the identification of the driest periods of the rainfall regime and the years of intense rains. For this study, the data were made available by the Ceará Meteorological and Water Resources Foundation through the historical series. Data tabulation and organization, as well as statistical calculations, used excel software. It was possible to identify the variability and irregularities in the rains of the Region and the influence of El Niño, intervening in the rains of the studied region.